2005
DOI: 10.1200/jco.2005.02.6252
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Geographic Variation in the Use of Hematopoietic Growth Factors in Older Women Receiving Breast Cancer Chemotherapy: Findings From a Large Population-Based Cohort

Abstract: Purpose-Hematopoietic growth factors have played a major role in preventing infection and shortening the duration of neutropenia in patients receiving cancer chemotherapy. Little information is available on how these growth factors are used in patients with cancer outside the clinical trial setting. We performed descriptive and exploratory analyses on the patterns and correlates of the use of hematopoietic growth factors in community-dwelling elderly patients.Patients and Methods-We identified 5,843 women from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Previous population studies expressed concern about counter-intuitive findings in factors associated with CSF administration, e.g., older women with higher co-morbidity indices had lower probability of receiving CSF. Studies also found that more severe tumor characteristics were associated with higher probability of PP-CSF administration [24,25]. In this study, initial univariate comparisons did indicate similar associations in age and clinical characteristics, though these associations resolved to statistical insignificance after more specified multivariate analysis.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous population studies expressed concern about counter-intuitive findings in factors associated with CSF administration, e.g., older women with higher co-morbidity indices had lower probability of receiving CSF. Studies also found that more severe tumor characteristics were associated with higher probability of PP-CSF administration [24,25]. In this study, initial univariate comparisons did indicate similar associations in age and clinical characteristics, though these associations resolved to statistical insignificance after more specified multivariate analysis.…”
Section: Discussionsupporting
confidence: 53%
“…Regional disparities in the administration of PP-CSF are substantial. Past studies have also shown significant regional variations [24,25]. Local coverage differences due to possible differences in ''Local Medical Review Policies'' (LMRPs) of the regional Medicare contractors might lead to differences in regional prescribing patterns [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19 A recent population-based study in older breast cancer patients reported substantial regional variation in filgrastim use. 23 Likewise, prior studies have found substantial variation in physicians' self-reported use of CSFs for prophylaxis of FN. 24 Additionally, prescribing patterns (i.e., the timing of initiation and duration of use) for filgrastim have been shown to vary from that used in the clinical trials in several community practice studies.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Three categories of variables were controlled for namelypatient socio-demographic, clinical (overall and tumorrelated), and therapeutic characteristics [10,32,34,[42][43][44][45]. Table 1 describes each characteristic and the corresponding variable.…”
Section: Potential Confounding Variablesmentioning
confidence: 99%